2017
DOI: 10.1007/s13320-017-0423-3
|View full text |Cite
|
Sign up to set email alerts
|

Large strain detection of SRM composite shell based on fiber Bragg grating sensor

Abstract: There may be more than 2% strain of carbon fiber composite material on solid rocket motor (SRM) in some extreme cases. A surface-bonded silica fiber Bragg grating (FBG) strain sensor coated by polymer is designed to detect the large strain of composite material. The strain transfer relation of the FBG large strain sensor is deduced, and the strain transfer mechanism is verified by finite element simulation. To calibrate the sensors, the tensile test is done by using the carbon fiber composite plate specimen at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Huang et al reported a long-period fiber grating (LPFG) optic sensor packaged with a hybrid mechanism of elastic attachment and gauge length change in a high-temperature environment. The maximum strain was as high as 15200 με (~1.5%) [9]. Zhang et al proposed an FBG sensor packaged by polydimethylsiloxane (PDMS) to monitor 2% strain of carbon fiber composite material on solid rocket motor [10].…”
Section: Introductionmentioning
confidence: 99%
“…Huang et al reported a long-period fiber grating (LPFG) optic sensor packaged with a hybrid mechanism of elastic attachment and gauge length change in a high-temperature environment. The maximum strain was as high as 15200 με (~1.5%) [9]. Zhang et al proposed an FBG sensor packaged by polydimethylsiloxane (PDMS) to monitor 2% strain of carbon fiber composite material on solid rocket motor [10].…”
Section: Introductionmentioning
confidence: 99%
“…However, many diagnostic technologies are still complicated [1]. For example, fiber Bragg grating sensor (FBG) is sensitive to strain and temperature, which needs to be pasted on the surface (or embedded inside the material) of the measuring material or structure [2,3]. For signal detection and fault diagnosis, applications like rail fastener gasket, hydraulic device seals, and aircraft composite structural parts, were inconvenient to disassemble from the product and re-install a certain amount of sensors for signal acquisition.…”
Section: Introductionmentioning
confidence: 99%